Feasibility of tumor-informed circulating tumor DNA for detecting minimal residual disease in surgically resected biliary tract cancer - Younghee Park; Kyung Su Kim; Hyunji Jo; Hwang-Phil Kim; Dong Soo Kyung; Youngeun Yoo; Seog Ki Min; Eun Mi Nam; Kyubo Kim (PLoS ONE, 2026)
Background We prospectively investigated the potential of tumor-informed circulating tumor DNA (ctDNA) for detecting minimal residual disease (MRD) in surgically resected biliary tract cancer (BTC). Methods Personalized panels were developed using individual variants identified from the whole-exome sequencing of surgical specimens from each patient. Two sequential blood samples, collected preoperatively and within 6 weeks after surgery, were analyzed. A positive ctDNA result was defined as the identification of two or more patient-specific mutations. Results A total of 18 patients were enrolled. However, 1 patient was excluded due to inoperability detected during surgery, and personalized target panels could not be created for 3 patients due to a low number of target variants, resulting in the analysis of 14 patients. There was a tendency for a higher preoperative ctDNA positivity rate in an advanced overall stage (100% in stage III-IV vs. 44.4% in stage I-II, p = 0.126) and node-positive disease (100% in node-positive vs. 60% in node-negative, p = 0.210). After a median follow-up of 17.4 months (range, 11.4–31.1), the 1-year and 2-year progression-free survival (PFS) rates were 78.6% and 58.2%, respectively. Changes in ctDNA positivity status were negative to negative in 3 patients (25.0%), positive to negative in 3 patients (25.0%), and positive to positive in 6 patients (50%). Additionally, there was a trend for an association between poorer PFS and both preoperative and postoperative ctDNA positivity. Among ctDNA-negative patients before surgery, no progression was observed; however, 5 out of 10 ctDNA-positive patients experienced progression. Postoperatively, only 1 out of 6 ctDNA-negative patients experienced progression, in contrast to 3 out of 6 patients with a positive ctDNA result. Conclusions Although limited by the small sample size, our results may indicate a possible role for tumor-informed ctDNA analysis in detecting MRD in surgically resected BTC and warrant further validation in larger studies.